(untitled) - Lewis, Beverly; 1949- (Minneapolis, Minn., 2005)
"Annie Zook--the preacher's eldest daughter--is expected to join the Amish church, but at 20 she is 'still deciding.' Because of the strict rules that guide the Plain community, she must continually squelch her artistic passion, although it has become her solace"--Provided by publisher.
Keywords: Fiction; Fiction; Amish; Women artists; Fiction; Children of clergy; Fiction; Bildungsromans